Maximizing the potential of sustainable aquatic food systems for global food security: key opportunities and challenges - Hasselberg, Astrid Elise; Frøyland, Livar; Kögel, Tanja; Markhus, Maria Wik; Plata, Javier; van der Meeren, Terje; Sørhus, Elin; Sanden, Monica; Lunestad, Bjørn Tore; Hannisdal, Rita; Olsen, Erik (Frontiers in Ocean Sustainability, 2024)
The development and management of our future aquatic food systems play a pivotal role in achieving the UN sustainable development goals (SDGs). While expanding aquatic food systems align with the ambitions of national 'blue economy' strategies, understanding challenges and opportunities is essential for successful expansion. Three globally relevant case studies—seaweed farming and harvesting, bivalve farming and harvesting, and tuna fisheries—were identified. A literature review revealed challenges and opportunities linked to UN SDGs related to poverty (1), hunger (2), health (3), gender equality (5), responsible consumption (12), climate action (13), and life below water (14). Although no single solution addresses all challenges, the cases emphasize that adapted spatial and ecosystem-based management offers pathways to address major challenges and capitalize on key opportunities.